Unbalanced Transportation Problem For Crude Palm Kernel Oil (CPKO) Distribution Cost Optimization Using ASM Modification Method - Dian Darmawan; Riri Syafitri Lubis (EduMatSains : Jurnal Pendidikan, Matematika dan Sains, 2025)
In the global agricultural sector, Indonesia is the largest producer of palm oil within the agricultural sector.  Palm fruit is then processed into palm oil. This research optimizes the distribution cost of crude palm kernel oil (CPKO) at Agrojaya Perdana by addressing transportation imbalances.  The study uses a Modified ASM method, which adds a dummy column to handle excess production capacity, followed by row and column reduction to identify optimal allocations. The initial solution from the Modified ASM method is then further optimized using the Stepping Stone method.  The results show a significant cost reduction of Rp 15,132,000.00 (approximately 2.251%) compared to the initial distribution cost of Rp 672,336,000.00, demonstrating the effectiveness of the combined Modified ASM and Stepping Stone methods in resolving transportation imbalances and optimizing distribution costs for PT. Agrojaya Perdana.